The art of self-beliefs. A Boudonian approach to social identity - Aguiar, Fernando (Papers. Revista de Sociologia, 2014)
In spite of recognizing that the concept of beliefs is a basic ingredient of our identity, Raymond Boudon neither developed a belief-based theory of social identity nor paid special attention to the concept. This article will attempt to shed some light on why Boudon excluded identity from his work and inquire if his social theory can be used to address the issue. We suggest that it is possible to build the concept of identity on Boudon’s model of action by defining identity as a special kind of belief – a belief about oneself or self-belief.